Dynamics of Correctional Institution Governance in Increasing The Meaning of Life of Inmates - Santoso, Iman; Indahdewi, Laudita (MSJ : Majority Science Journal, 2024)
This study examines the role of correctional institutions in improving the meaning of life of prisoners through the dynamics of correctional institution governance in Sleman Class IIB. The main focus of this study is to evaluate how a comprehensive rehabilitation program-including skills training, education, mental health support, and spiritual activities-can improve inmates' quality of life and meaning of life. This research used a qualitative method with a literature study approach and interviews to collect primary data from prisoners and officers at Sleman Class IIB. The results show that a holistic approach to rehabilitation, which includes skills development, education, and health services, has had a positive impact on the well-being and self-development of prisoners. Despite challenges related to overcapacity, measures such as facility additions and parole programs during the pandemic have helped improve the living conditions of inmates. Active participation of prisoners in decision-making and ongoing training for prison officers also play an important role in creating an enabling environment for effective rehabilitation. The study concludes that good governance and a holistic approach can significantly improve the meaning of prisoners' lives and make Sleman Kelas IIB a model for other correctional institutions in creating a more humane and productive system.